Interfacial Structures in Bubbly-to-Slug Transition Flows in a Duct. (1st February 2020) - Wang, Guanyi; Zhu, Qingzi; Ishii, Mamoru
Abstract: As a critical closure equation to the two-fluid model and an important tool to characterize the two-phase-flow interfacial transport, the interfacial area transport equation (IATE) was formulated by taking various physical mechanisms causing interfacial area change into account. To fulfill the dynamic prediction advantage of IATE and further replace the flow regime–based constitutive relations, the IATE model should be validated by transition data to ensure model reliability and robustness. Air-water experiments are performed in bubbly-to-slug transition flows in a 200 × 10-mm narrow rectangular duct. Four-sensor conductivity probes are used to measure the local void fraction, interfacial area concentration (IAC), and bubble velocity at three axial locations. The void fraction distribution changes significantly with the flow developing. Flow conditions with a similar area-averaged void fraction but different superficial mixture velocities are compared, and it is found that the superficial mixture velocity significantly affects the IAC. In addition, the two-group IATE model for narrow rectangular channel is evaluated using the collected data. The average relative error for the total IAC prediction is 11.4%, but the group II IAC is overestimated for most flow conditions.